EFEKTIVITAS TERAPI MEDITASI MINDFULNESS TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI USIA LANSIA 60-70 TAHUN DI DESA KENANGAN BARU - Krisdamayanti Zai; Lam Murni Sagala (Indonesian Trust Nursing Journal, 2026)
Hypertension is a common health problem in the elderly and can be exacerbated by stress. Mindfulness meditation is a non-pharmacological therapy that can help lower blood pressure through relaxation and stress management. This study aims to determine the effectiveness of mindfulness meditation therapy on reducing blood pressure in elderly people with hypertension aged 60–70 years in Kenangan Baru Village. The study used a quasi-experimental design with a two-group pretest–posttest control design on 40 respondents, consisting of 20 in the intervention group and 20 in the control group. The intervention group was given 15–30 minutes of mindfulness meditation for 6 times a week. Blood pressure was measured before and after treatment. Analysis was performed using the Shapiro–Wilk test, Wilcoxon Signed-Rank Test, and Mann–Whitney U Test. The results showed a significant decrease in blood pressure in the intervention group (p = 0.011) and insignificant in the control group (p = 0.233). Comparison between groups showed significant differences in systolic (p < 0.001) and diastolic (p = 0.013) blood pressure. In conclusion, mindfulness meditation therapy has been proven to be effective in reducing systolic and diastolic blood pressure in elderly people with hypertension, so it can be recommended as a non-pharmacological intervention in nursing services to help control hypertension in the elderly.